The Analysis Study of Hemolysis due to Blood Warming during Blood Transfusion : A Comprehensive Systematic Review - Nugroho, Fajar Prianto; Indra, Muhammad (The International Journal of Medical Science and Health Research, 2024)
Introduction: Over recent decades, blood transfusion practices have significantly evolved, particularly in trauma care, surgery, obstetrics, and intensive care settings. This systematic review explores the relationship between blood warming, pressure, and hemolysis, aiming to provide evidence-based guidelines for safe transfusion practices. Methods: This systematic review follows PRISMA 2020 guidelines. We include studies from 2004 to 2024, focusing on hemolysis rates related to blood warming, transfusion outcomes, and safety thresholds for warming temperatures and pressures. A search across PubMed, ScienceDirect, and Sagepub yielded studies meeting these criteria. Data extraction focused on study characteristics, warming techniques, hemolysis rates, and outcomes. Results: Most studies indicated that blood warmers effectively raise temperatures without significantly increasing hemolysis under controlled conditions. However, higher flow rates and temperatures above 37°C increase the risk of hemolysis. While current blood warming devices are generally safe, there is variability in their performance based on flow rates and clinical settings. Conclusion: Blood warming devices are effective tools for preventing hypothermia during transfusions but must be carefully used to avoid hemolysis. Further research is needed to optimize protocols for different clinical contexts and patient populations to ensure safe and effective transfusions